2018
DOI: 10.1002/dmrr.3011
|View full text |Cite
|
Sign up to set email alerts
|

Low serum creatinine predicts risk for type 2 diabetes

Abstract: These findings indicate that serum creatinine concentration is inversely related to incident T2DM in both men and women. Measuring serum creatinine may assist in the early detection of individuals at high risk of developing T2DM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 39 publications
2
18
1
Order By: Relevance
“…In the stratified analyses, we observed that the serum creatinine–diabetes association did not differ by BMI or smoking status, which is consistent with previous studies. Furthermore, we found no effect modification by chronic diseases (for example, hypertension or dyslipidemia).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…In the stratified analyses, we observed that the serum creatinine–diabetes association did not differ by BMI or smoking status, which is consistent with previous studies. Furthermore, we found no effect modification by chronic diseases (for example, hypertension or dyslipidemia).…”
Section: Discussionsupporting
confidence: 91%
“…The present findings are consistent with those studies using baseline creatinine only. In a 4‐year follow‐up study of Japanese male workers ( n = 8,570), the adjusted odds ratio of diabetes was 1.91 for the participants with creatinine 0.40–0.60 mg/dL compared with 0.71–0.80 mg/dL.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Although serum Cre was not associated with incident diabetes in this study population, previous studies have shown that low Cre is associated with the presence of [40][41][42][43] or incident diabetes [44][45][46][47]. These studies showed that the risk of incident diabetes in the lowest serum Cre group was higher than that in highest serum Cre group [44][45][46][47].…”
Section: Discussioncontrasting
confidence: 74%